Tolerance for three commonly administered COVID-19 vaccines by healthcare professionals - Melanson, Stacy E. F.; Zhao, Zhen; Kumanovics, Attila; Love, Tanzy; Meng, Qing H.; Wu, Alan H. B.; Apple, Fred; Ondracek, Caitlin R.; Schulz, Karen M.; Wiencek, Joseph R.; Koch, David; Christenson, Robert; et al. (Frontiers in Public Health, 2022)
Importance: Most healthcare institutions require employees to be vaccinated against SARS-CoV-2 and many also require at least one booster. Objective: We determine the impact of vaccine type, demographics, and health conditions on COVID-19 vaccine side effects in healthcare professionals. Design: A COVID-19 immunity study was performed at the 2021 American Association for Clinical Chemistry Annual Scientific meeting. As part of this study, a REDCap survey with cascading questions was administered from September 9, 2021 to October 20, 2021. General questions included participant demographics, past and present health conditions, smoking, exercise, and medications. COVID-19 specific questions asked about SARS-CoV-2 vaccine status and type, vaccine-associated side effects after each dose including any boosters, previous infection with COVID-19, diagnostic testing performed, and type and severity symptoms of COVID-19. Results: There were 975 participants (47.1% male; median age of 50 years) who completed the survey. Pfizer was the most commonly administered vaccine (56.4%) followed by Moderna (32.0%) and Johnson & Johnson (7.1%). There were no significant differences in vaccine type received by age, health conditions, smoking, exercise, or type or number of prescription medications. Side effects were reported more frequently after second dose (e.g. Moderna or Pfizer) (54.1%) or single/only dose of Johnson & Johnson (47.8%). Males were significantly more likely to report no side effects (p<0.001), while females were significantly more likely to report injection site reactions (p<0.001), fatigue (p<0.001), headache (p<0.001), muscle pain (p<0.001), chills (p=0.001), fever (p=0.007), and nausea (p<0.001). There was a significant upward trend in participants reporting no side effects with increasing age (p<0.001). There were no significant trends in side effects among different races, ethnicities, health conditions, or medications. In multivariate logistic regressions analyses, the second dose of Moderna was associated with a significantly higher risk of side effects. Conclusions and Relevance: Younger people, females, and those receiving the second dose of Moderna had more COVID-19 vaccine side effects that per self-report led to moderate to severe limitations. As reported in other studies, the increase in side effects from Moderna may be explained by higher viral mRNA concentrations but be associated with additional protective immunity.